Adaptive cascaded equalizer for unmanned aerial vehicle data link - Tian, W.; Liu, Jian; Wang, S. (2017)
© 2017 IEEE. In order to solve the multipath effect and non-ideal channel characteristics for unmanned aerial vehicle data link, this paper introduces the design of adaptive cascaded equalizer and its FPGA implementation. By cascading constant modulus algorithm (CMA) equalizer, digital phase locked loop (PLL) and decision feedback equalizer (DFE), adaptive cascaded equalizer achieves convergence through two manageable and independent stages to optimize equalization. Test results show that compared to traditional equalizers, the adaptive cascaded equalizer can track channel variation rapidly and has high convergence speed, good stability and practicability.